تطوير معجم الاقتران اللفظي العربي وتوظيفه فى تعليم الإنشاء الموجه لطلبة الجامعة : Developing an Arabic Collocation Dictionary and Its Pedagogical Application in Teaching Insyā’ Muwajjah to University Students - Moh. Munir; Rizka Eliyana Maslihah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2026)
This article aims to describe the outcomes of Insyā’ Muwajjah learning for university students through the use of an Arabic collocation dictionary. The study employed a mixed-method approach with a Sequential Exploratory Design integrating Research and Development (R&D) and qualitative methods. The Borg and Gall R&D model was used to develop an Arabic collocation dictionary tailored to students’ needs, while the qualitative approach examined its implementation through classroom observations and interviews. The novelty of this study lies in the application of an Arabic collocation dictionary specifically designed for Insyā’ Muwajjah learning. The findings indicate that the dictionary effectively supports students in improving their Arabic writing skills through the integration of Arabic collocations into learning materials and writing exercises based on specific themes.